KAJI TINDAK AKSELERASI INOVASI TEKNOLOGI SPESIFIK LOKASI MENDUKUNG PENINGKATAN PRODUKSI DAN PRODUKTIVITAS USAHATANI - Rooganda Elizabeth; Delima Hasri Azahari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This paper aims to comprehensively address the important role of accelerating the application of location-specific technological innovations as one indicator of realizing agricultural and rural development. The implementation of agricultural development has had a real impact on socio-economic changes in rural communities. Food security and farmer and rural welfare still remain a strategic problem. Programs and policies that introduce various technologies to increase rice production and productivity have been carried out by the government. Some of them are about the Green Revolution, the Bimas Inmas program, the rice SL-PTT program, the rice intensification program (IP-400, SRI, P4 MI and others. This paper is part of various research results, one of which is PATANAS: Indicators of Agricultural and Rural Development, which is supported and enriched with various data and information related to the purpose of writing. The use of organic fertilizers is highly recommended because it is very useful for improving soil structure as a source of micro nutrients and as a medium for soil microbes development. During the past decade the use of seeds labeled by farmers has increased, including the existence of aid programs and subsidized seed prices. Labeling whether or not rice seeds are used by farmers is positively correlated with procurement source. Empirical facts show that the increasing conversion of agricultural land to non-agriculture threatens the existence of the agricultural sector in terms of national food security. Innovations implementation considering the specific location should be carried out as early as possible